Variation in Activity of Pepsin Extracted from Buffalo Stomach Mucosa: Pepsin Extraction from Buffalo Stomach Mucosa - Firdous, Shamma; Javed, Akmal; Miraj, Sadia; Ejaz, Nusrat (Biological Sciences - PJSIR, 2013)